Effects of neonatal surgical castration and immunocastration in male pigs on blood T lymphocytes and health markers. (17th April 2014) - Leclercq, C.; Prunier, A.; Merlot, E.
Abstract : Surgical castration in pig husbandry is criticized for welfare reasons. Thus, it is necessary to evaluate alternative ways of rearing male pigs, such as entire or immunocastrated animals. Immunocastration is a vaccination directed against gonadotropin-releasing hormone (GnRH) to suppress the production of sexual hormones. This study aimed at investigating the effects of these two methods of castration in comparison with intact male pigs on blood T-lymphocyte subsets and function, the immunoglobulin (Ig) response to an influenza vaccine and health markers during sexual development. A total of 70 animals were allocated to three experimental groups: entire (E), surgically castrated at 5 to 6 days of age (SC), and immunized against GnRH at 3 and 4 months of age (IC). Blood samples were collected at 3, 4 and 5 months. At slaughter, global health status and body and spleen weights were measured. Results showed that SC male pigs had fewer blood lymphocytes than E pigs at 4 and 5 months ( P <0.05), whereas IC pigs did not differ significantly from E pigs. The percentages of CD3 +, CD3 + CD4 + and CD3 + CD8 + lymphocytes were not altered by treatment ( P >0.1). Compared with E pigs, the SC pigs had a higher percentage of CD3 + CD4 + CD8 + cells at 4 months, whereas the IC pigs had a higher percentage at 5 months ( P <0.05). Regarding γδ T cells, SC pigs had a lower percentage than E pigs at 4 and 5 months ( P <0.05), whereas IC pigs did not differ significantly from E pigs at any age. However, there were no consequences on T-lymphocyte proliferation and total IgG or anti-influenza Ig. At slaughter, relative spleen weight was decreased in IC pigs, whereas pneumonia score was decreased in SC pigs relatively to E pigs. Overall, no clear functional consequences of either method on commercial pig immune abilities were demonstrated, but more investigations are required to ascertain this conclusion.